Healthcare Data Analysis Through Business Intelligence: A Case Study With Power BI - Cahyaningrum, Avikatria; Nuryana, I Kadek Dwi (Universitas Negeri Surabaya, 2026)
This research aims to analyze hospital health data with the application of Power BI-based Business Intelligence (BI) to support a more precise and efficient decision-making process. The research data is taken from a public repository that provides a hospital management system database structure with complex inter-table relationships. The initial stages were carried out with the ETL (Extract, Transform, Load) process to integrate and clean the data before being entered into the data warehouse with the star and galaxy schema model. Next, analysis was conducted using Online Analytical Processing (OLAP) for medical service usage and other trends. In addition, the application of data mining using the Random Forest algorithm is also carried out for the classification of hospital busyness levels and prediction of patient re-visits based on historical data.